Entrepreneurial backgrounds, human capital and start-up success - Rui Baptista; Murat Karaöz; Joana Mendonça (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We examine whether founders backgrounds influence new firm survival in the early years after start-up. We develop hypotheses linking founders back-grounds to pre-entry capabilities associated with entrepreneurial human capital, highlighting the cases of spin-offs and habitual entrepreneurs. The subject of unemployment-driven entrepreneurship is also explored. We find that specific human capital more frequently found in spin-off founders plays a key role in enhancing survival chances, while more general forms of human capital may help inexperienced entrepreneurs overcome the barrier posed by the critical early years after start-up.
Keywords: D21; L10; M13; 330; Founders backgrounds; Human capital; Start-up Success; Pre-entry capabilities; Spin-offs; Habitual entrepreneurs; Unternehmensgründung; Unternehmensentwicklung; Unternehmer; Humankapital; Berufserfahrung; Portugal